EFFECT OF SOIL AND FOLIAR APPLICATION OF IRON CHELATE ON NUTRIENT BALANCE IN LENTIL (Lens esculenta L.) BY USING MODIFIED DRIS EQUATION - Dalshad .A.Darwesh (Mesopotamia Journal of Agriculture)
A pot experiment was conducted to investigate the influence of two different Fe sources (Fe-EDTA and Fe-EDDHA) were sprayed on to the leaves and applied to the soil in levels were involved 0, 10, 20 and 30mg.l-1 both fertilizers were sprayed to leaves two times, the interval date was 20 days and during spraying the soil surface were covered with plastics to prevent Fe contamination. The results indicated that there were significant effect (P<0.01) of the combination between types, concentration, and method of Fe application on total dry matter and on the concentration of N, P, Ca, Mg, K and Fe. The higher values of 6.24g.pot-1 and 30.98, 3.54, 33.81, 28.43mg.g-1, 246.67mg.kg-1 were recorded from combination treatment (F2M2L2) respectively, however the data revealed that the lowest nutrient balance index was recorded from combination treatment (F2M2L2) and attained 34.58, while the higher NBI of(1028.45) was recorded in combination treatment (F1M2L3), also the result indicated that there are negative correlationship between the nutrient balance index and total dry weight were attained (R= -0.72).